Advances and Perspectives of Peptide and Polypeptide‐Based Materials for Biomedical Imaging. Issue 5 (4th March 2021) - Lv, Mingchen; Jan Cornel, Erik; Fan, Zhen; Du, Jianzhong
Abstract : Biomedical imaging is an effective tool to reveal internal structures beneath the skin. Such tools are of great importance for disease diagnosis and treatment. Various small molecules, polymers, and micro‐ or nanomaterials have been applied as imaging agents for contrast enhancement. Peptide‐ and polypeptide‐based materials have been designed and developed for enhanced and multifunctional imaging, due to their excellent biocompatibility and diverse biofunctionality. This review aims to summarize recent advances in peptide‐ and polypeptide‐based materials for X‐ray computed tomography (CT), magnetic resonance imaging (MRI), fluorescence imaging (FLI), positron emission tomography (PET), single‐photon emission computed tomography (SPECT), and multimodal imaging. In addition to biomedical imaging, peptide‐ and polypeptide‐based materials have also been endowed with therapeutic functions for disease theranostics. This review is concluded with a perspective on future peptide‐ and polypeptide‐based materials for biomedical imaging. Abstract : Due to the excellent biocompatibility and diverse biofunctions, peptide‐ and polypeptide‐based materials have been designed and developed for enhanced and multifunctional bioimaging. Herein, recent advances and future perspectives of peptide‐ and polypeptide‐based materials for computed tomography, magnetic resonance imaging, fluorescence imaging, positron emission tomography, single‐photon emission computed tomography, and multimodal imaging toward disease diagnosis and treatment are summarized and discussed.